Assessment of energy efficient rocket stoves contribution on deforestation control in Tanzania, a case study of Chamwino district in Dodoma region - Gerome, Annamaria Cornelius (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University